Inteligencia Emocional en estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Sigcho Ramón, Janeth Elizabeth (2022)
The research was proposed to determine the level of development of emotional intelligence in students of the major of Psychopedagogy at the National University of Chimborazo. I considered that emotional intelligence is the development and management of their own and others' emotions. For the research development, a quantitative approach was established, with a non-experimental design, for the correlational, cross-sectional type field because the instrument was applied only once and at a determined moment as a population to the Faculty of Human Sciences students of Education and Technologies. The sample is non-probabilistic and intentional of 155 students between men and women of second, third, fourth, seventh, and eighth semesters. For data collection, the psychometric technique was used with the Trait Meta-Mood Scale (TMMS-24 from Fernandez-Berrocal, 1994), adapted online, which consists of three dimensions of Emotional Intelligence: Emotional Perception, Emotional Understanding, and Emotional Regulation. To conclude, most students in the psychopedagogy school have an adequate level of development concerning dimensions, perception, comprehension, and emotional regulation, demonstrating the ability to perceive, understand, and regulate their emotions and those of others.